2006
DOI: 10.1108/09615530610653064
|View full text |Cite
|
Sign up to set email alerts
|

Jet entrainment minimization in an air curtain of open refrigerated display case

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Figure 4 shows the velocity profile at different Reynolds numbers. It is shown [12] that the Top-Hat profile is the best practical profile that can exist at the DAG for reducing the infiltration rate. Carbon dioxide (CO 2 ) has been used as the tracer gas in the current work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4 shows the velocity profile at different Reynolds numbers. It is shown [12] that the Top-Hat profile is the best practical profile that can exist at the DAG for reducing the infiltration rate. Carbon dioxide (CO 2 ) has been used as the tracer gas in the current work.…”
Section: Resultsmentioning
confidence: 99%
“…They have shown that this hybrid approach can effectively quantify the effect of individual flow/geometrical parameters on the air curtain performance. They have also mentioned that certain operating conditions can result in improved performance of an air curtain [12,13]. Field et al [14,15] studied circulating air curtains of a display case by the PIV visualization.…”
Section: Nomenclaturementioning
confidence: 99%
“…Obviously, the amount of infiltrated warm air should be kept to a minimum to conserve energy for running the cooling cycle to maintain a prescribed cold air temperature that is being driven to the DAG and the back panel. There have been numerous studies by Navaz et al (2002Navaz et al ( , 2004Navaz et al ( , 2006aNavaz et al ( , b, 2007a to identify parameters that can affect the infiltration rate in open refrigerated display cases. They have used a hybrid numerical and experimental approach to calculate the infiltration rate of the warm air into these display cases.…”
Section: Application Of Ann To An Open Refrigerated Display Case-steamentioning
confidence: 99%
“…This year Navaz et al [32] have presented a work to address the effects of velocity profile at the discharge air grill on the amount of entrained air into an open refrigerated display case. The study was carried out using experimental techniques (DPIV and LDV) and also by means of CFD simulations.…”
Section: Cui and Wangmentioning
confidence: 99%